The role of change management in corporate digitalization: The relevance of Kotter’s eight-step change model within IT/digitalization projects - Mancini, Leonardo Amaral (2023)
During the current digital transformation, corporate digitalization projects are not only gaining ground but becoming a constant in organizations with the ultimate goal of maintaining competitiveness. However, for this corporate digitalization to be successful and to meet the expectations of the stakeholders, there is a need for a suitable management of this digital change. For this reason, change management plays an increasingly central role in successful corporate digitalization. Therefore, it is imperative to understand whether the established approaches are effective for managing corporate digitalization. The aim of the research in this work is to examine the relevance of the reference model in the field of change management, John P. Kotter's eight-stage model, in the context of corporate digitalization and, at the same time, to identify the success factors from practice for such projects. In order to achieve the goal of the research, a qualitative research methodology was chosen. In-depth interviews were conducted with experts that have many years of project experience at the interface of change management and corporate digitalization. The results of the work demonstrate that Kotter's reference model does contain important elements of a change project but does not focus enough on the essential pillars of digital change: communication, agility and participation.